Elemental Composition of Sand Puya Processed through Alkali Fusion with Sodium Hydroxide - Zaharah, Titin Anita; Lestari, Agustina Duwan; Sembiring, Albert; Silalahi, Imelda Hotmarisi (ALCHEMY:Journal of Chemistry, 2024)
Puya sand is a well-known name by people in West Borneo, for remainder sand from gold mining conducted by local people, contains a mixture of minerals consist of elements, such as zirconium, silicon, iron, titanium and rare earth metals.  In order to recover and separate the minerals, an initial chemical process, i.e., alkali fusion reaction with sodium hydroxide has been conducted.  Puya sand that have been pre-treated, called magnetic sand (pasir tertarik magnet, PTM) was reacted with NaOH in various mass of PTM:NaOH 1:0.5, 1:1 and 1:2 as well as various temperature of 550 °C, 600 °C , 700 °C and 800 °C for each concentration variants. The X-ray diffraction (XRD) analysis showed that the main mineral found in PTM is zirconium silicate, ZrSiO4 which is crystalline, however it became an amorph material after it was reacted with NaOH at 550 °C. In a mass ration of PTM:NaOH of 1:2 at 550 °C, the reaction product calcinated at 800 °C appeared to form hematite, zirconia and silica shown by the XRD analysis. The analysis of X-ray fluorescence (XRF) demonstrated a different elemental composition in a different reaction condition. Zirconium silicate likely was decomposed to zirconate and silicate assigned by a high Zr/Si ratio, seen more obvious at the temperature of 700 °C, in which the highest Zr/Si ratio was found at the mass ratio of PTM:NaOH, 1:2. The fusion reaction between PTM and NaOH at 600 °C and PTM:NaOH of 1:2 resulted in a material with the highest concentration of iron element relative to other elements. Reaction undertaken at 700 °C and mass ratio of PTM:NaOH of 1:0.5 gave a product with the highest concentration of titanium elements or oxide. Depends on the mineral target aimed to decompose, the condition of alkali fusion reaction is an important aspect to take into account.